Micro but mighty: Critical success factors for sustainable urban micro-entrepreneurship in Terengganu - Awang, Norafzan; Samsurijan, Mohamad Shaharudin; Awang, Norbahiyah; Zahri, Fatin Alia; Ambak, Azlinah; Ambak, Azlinah (Journal of Islamic, Social, Economics and Development, 2025)
Micro-entrepreneurship is vital to inclusive development, yet its sustainability isemi-peripheral economies remains underexplored. This paper develops a context-sensitive framework of Critical Success Factors (CSFs) for urban micro-entrepreneurship in Terengganu, Malaysia, where institutional gaps, limited infrastructure, and cultural embeddedness create distinctive challenges. Guided by the Resource-Based View (RBV) and Institutional Theory, the framework integrates four domains: financial and entrepreneurial competencies, digital readiness and innovation, socio-psychological enablers, and institutional support. Unlike conventional CSF models from industrialized contexts, it highlights resilience, religious identity, and community trust as mediating resources of sustainability. Drawing on a synthesis of literature and contextual insights, the study reconceptualizes sustainability as the interaction of tangible and intangible factors, introduces socio-psychological enablers into RBV–Institutional Theory integration, and proposes localized interventions such as mosque-based mentoring and gender-sensitive digital inclusion. By situating entrepreneurship within localized realities, the study challenges urban-centric models and advances an agenda for resilient micro-enterprise sustainability.